Efficiency and kinetics of conventional pollutants and tetracyclines removal in integrated vertical-flow constructed wetlands enhanced by aeration. (1st November 2020) - Li, Xuhui; Zhu, Weigang; Meng, Gengjian; Zhang, Chaosheng; Guo, Ruichao
Abstract: The integrated vertical-flow constructed wetland (IVCW) is considered as a potential alternative for domestic wastewater treatment of towns and small cities. Oxygen supply is the main limitation of pollutants removal in IVCWs. In the present study, a field experiment was conducted to evaluate the capacity and kinetics of pollutants removal in IVCWs with/without artificial aeration. Two IVCWs constructed with Canna indica and Phragmites australis were running in continuous flow to remove high concentrations of conventional pollutants and low concentrations of tetracyclines (TETs), which are at similar levels of domestic wastewater. The results showed that IVCWs had a good performance on COD, phosphorus, and TETs with removal efficiencies over 80%, 64%, and 75%, respectively, with a hydraulic retention time (HRT) of 3.0 d. However, the removal of nitrogen was limited, showing as TN removal efficiency of about 30%. The IVCW with Phragmites australis had a higher removal efficiency and rate. A kinetics based on Monod Equation and solved with Matlab 2018a could describe the degradation of conventional pollutants. Artificial aeration improved the oxygen supply and remarkably raised the removal capacity for COD, N, and P in IVCWs. The q1/2 values, which was defined as the average removal loading before half of the pollutants was removed and represented the removal capacity without limitation of pollutants concentration, were increased by 5–30 times after aeration. In conclusion, IVCWs could remove conventional pollutants and TETs simultaneously showing a great potential in domestic wastewater treatment. Artificial aeration enhanced removal capacity of IVCWs on conventional pollutants while showed little influence on TETs. Graphical abstract: Image 1 Highlights: Effluent of the integrated vertical-flow constructed wetlands (IVCWs) with aeration meet discharge standard in China. Aeration enhanced the conventional pollutants removal capacity by 5–30 times. Aeration had little influence on tetracyclines removal. Monod kinetics balanced the accuracy and simplicity.